Gereja yang Bertahan Hidup: Kairos dan Eskatologi dalam Paul Tillich dan Raimon Panikkar serta Eklesiologi Pascapandemi - Nindyo Sasongko (Veritas : Jurnal Teologi dan Pelayanan, 2022)
This research investigates the relationship between the biblical notion of kairos, eschatology, and ecclesiology amid the struggle for survival in the postpandemic life. Drawing upon Paul Tillich and Raimon Panikkar, this article sketches a postpandemic ecclesiology called “kairotic ecclesiology.” The church must understand that it exists as a community that participates in, loves, and transforms life. Because of its indissoluble relation to history and reality, a kairotic community loves and defends life. This kairotic ecclesiology is an ontological search for the church to say “Yes” to life and “No” to death. Firstly, this article sketches kairos in Tillich and Panikkar. Then, this article sketches what I call the ecclesiology of survival, an ecclesiology characterized by resilience, interrelation, and irruption. Finally, I shall draw ethical implications for postpandemic churches.